Heart damage in ankylosing spondylitis - A A Godzenko; A G Bochkova; Y O Korsakova; N V Bunchuk; E S Mach (Научно-практическая ревматология)
Objective. To study heart damage in pts with ankylosing spondylitis (AS) by ECG and echocardiography (EchoCG). Material and methods. 344 pts with definite AS not older than 60 years without comorbid cardiac diseases examined in the Institute of rheumatology during 2005-2008 were included. ECG with 12 leads was performed in all pts and transthoracic EchoCG – in 101 pts. Results. Rhythm and conductivity disturbances were revealed in 67 from 344 (19,5%) pts: atrioventricular (a/v) heart block was present in 20 (5,8%) pts (16 had 1, 2 – 2 and 3 – 3 stage of a/v heart block). 27 (7,8%) pts had intraventricular heart block. EchoCG signs of aortal valve changes were revealed in 45 from 101 (44,5%) pts: thickness or dilatation of aorta – in 36 (35,6%), aortal valve cusps thickness – in 32 (31,7%), mitral – in 15 (14,8%). Local thickness in the form of a comb beneath aortal valve on the back wall of aorta basis at the site of its junction with basis of mitral anterior cusp – “subaortic bump” was found in 10 (10%) pts. Frequency of a/v heart block among pts with changes of aorta and cardiac valves was significantly higher than in pts without such changes. On the other hand frequency of aorta and cardiac valves changes in pts with a/v heart block was significantly higher than in pts without a/v heart block (p=0,0027) what shows relationship between conductivity disturbances and aorta and cardiac valves damage in AS. Conclusion. Cardiac pathology in AS is characterized by frequent (44,5%) damage of aorta basis and aorta-mitral junction zone in combination with thickness of aortal and mitral valves and conductivity disturbances.